Bulked segregant analysis identifies molecular markers associated with early bulking in cassava (Manihot esculenta Crantz) - Olasanmi, B; Akoroda, M.O.; Okogbenin, Emmanuel; Egesi, Chiedozie N.; Kahya, SS; Onyegbule, O; Ewa, F.; Gutiérrez, J.; Ceballos, H.; Tohme, Joseph M.; Fregene, Martin A. (Springer, 2014)
Late root bulking is a major factor leading to rejection and abandoning of improved cassava genotypes in sub-Saharan Africa. Early bulking (EB) varieties shorten the growth period from planting to harvesting, better fit into environments with short rainy season, and reduce exposure to biotic and abiotic stresses thereby increasing productivity. This study was carried out to identify molecular markers linked to EB in cassava. Nine cassava hybrid populations (COB-1–COB-9) were developed using six elite varieties (TMS 30572, TMS 97/2205, TMS 98/0505, TMS 30555, NR 8212 and NR 8083) from the African cassava germplasm as parents. The progeny in each of the nine populations (101–272 genotypes per population) were evaluated for EB at 7 months after planting at seedling, clonal, and preliminary stages of breeding evaluation at Umudike. The parameters measured are fresh root yield, harvest index, fresh shoot weight and number of storage roots per plant. The progeny in each of the nine populations were genotyped at 542 simple sequence repeat (SSR) marker loci. Bulked segregant analysis was used to identify the SSR markers associated with EB in the populations. Nine SSR markers (SSRY 106, (ESTs)SSRY 292, SSRY 239, (ESTs)SSRY 7, NS 194, (ESTs)SSRY 47, SSRY 63, SSRY 250, and NS 323) were found to be closely linked (r = 0.3–0.5; p < 0.05) to EB in six of the nine hybrid populations. Seven of the markers with 10 % or more coefficient of determination (R2) were linked to major quantitative trait loci associated with EB in cassava. The molecular markers identified in this study provide useful materials to select for EB in cassava and for further target-traits-improvement by pyramiding.